Histological and histochemical characterization of the musk gland in forest musk deer (Moschus berezovskii): a preliminary study - Qianyi Wang; Chunyu Han; Dong Zhang; Yuning Liu; Yunyun Gao; Haolin Zhang; Defu Hu (European Journal of Histochemistry, 2025)
Musk is a biologically valuable secretion from the musk gland of male musk deer, with significant economic and medicinal importance. Due to severe decline and depletion of wild musk deer population, captive breeding of musk deer has become the primary approach for sustainable musk production. So far, the histological structure and secretion mechanism of the musk gland remain incompletely understood. In this study, we employed histological and immunohistochemical (IHC) techniques, along with three-dimensional (3D) tissue reconstruction, to systematically analyze the cellular composition and secretory functions of the musk gland in forest musk deer (Moschus berezovskii). Our results revealed that the musk gland was primarily composed of acinar structures containing two distinct glandular cell (GC) types based on the histological observation. IHC results showed type I glandular cells (GCIs) predominantly expressed GALNT7 while type II glandular cells (GCIIs) mainly expressed BMP6. The 3D reconstruction demonstrated structural heterogeneity along the gland's longitudinal axis, with the proportion of the acinar area varying between 40% and 65%. This is the first time that a detailed 3D view of musk gland in forest musk deer has been shown, which provides essential histological insights into musk gland function in this species. These preliminary observations may provide useful groundwork for future investigations into the regulatory mechanisms of musk secretion.